2018
DOI: 10.1111/jcpt.12743
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for persistent methicillin‐resistantStaphylococcus aureusbacteraemia

Abstract: Given the heterogeneity of the data, a preferred regimen has not emerged. Prescribers must take into consideration recent exposure, source control, and available synergy and clinical data. Further comparative trials are needed to establish a preferred regimen and the creation of a universal treatment algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 97 publications
(197 reference statements)
0
39
0
3
Order By: Relevance
“…It is an important observation since vancomycin remains the cornerstone for management of MRSA infection (Lewis et al 2018). Its efficacy is now being questioned with the emergence of strains of S. aureus that display intermediate resistance or complete vancomycin resistance and occasionally treatment failures (Holmes and Howden 2014;Lewis et al 2018). High levels of resistance were observed to clindamycin (68.8%, 11/16) and erythromycin (75.0%, 12/16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is an important observation since vancomycin remains the cornerstone for management of MRSA infection (Lewis et al 2018). Its efficacy is now being questioned with the emergence of strains of S. aureus that display intermediate resistance or complete vancomycin resistance and occasionally treatment failures (Holmes and Howden 2014;Lewis et al 2018). High levels of resistance were observed to clindamycin (68.8%, 11/16) and erythromycin (75.0%, 12/16).…”
Section: Resultsmentioning
confidence: 99%
“…Clindamycin is a bacteriostatic antimicrobial and inhibits bacterial toxin production. Clindamycin can be indicated for management of S. aureus infections including those caused by MRSA (Lewis et al 2018). It is important to note that high levels of erythromycin resistance in S. aureus/MRSA isolates induce clindamycin resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a recent article by Zheng et al [4] found that the combinations of TZP with VAN and cefazolin with VAN prevented VAN intermediate resistance development in vitro [4]. Clinical investigations of adjuvant β-lactam therapy in combination with VAN demonstrated that combination therapy accelerates the time to bacterial clearance [5].…”
Section: Introductionmentioning
confidence: 99%